The United Nations Convention on Migrant Workers’ Rights. Obstacles, opportunities and perspectives - de Guchteneire, Paul; Pécoud, Antoine (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
This article analyses the obstacles encountered by the UN International Convention on the Protection of the Rights of All Migrant Workers and Members of their Families, the most comprehensive international treaty in the field of migration and human rights, which has however been ratified by only 39 states. It gathers evidence from major destination states in Africa, Asia, Europe and the Americas and outlines three main sources of difficulties stemming from the influence of market forces, security and sovereignty on migration policies. It concludes by an investigation of the place of the Convention and of migrants, rights in recent initiatives taken by the international community in the field of migration management